2019
DOI: 10.3390/molecules24173113
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Polyethylene-Based Composites Reinforced with Alkali and Palmitoyl Chloride-Treated Coffee Silverskin

Abstract: This work investigates the feasibility of using coffee silverskin (CSS) as a reinforcing agent in biobased polyethylene (BioPE) composites, by adding it in bulk and thin film samples. The effect of two different treatments, alkali bleaching (CSS_A) and esterification with palmitoyl chloride (CSS_P), on mechanical, thermal, morphological and water absorption behavior of produced materials at different CSS loading (10, 20 and 30 wt %) was investigated. A reactive graft copolymerization of BioPE with maleic anhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 54 publications
4
31
0
1
Order By: Relevance
“…Some previous studies have reported similar mechanical properties of green composites based on coffee waste derived fillers. For instance, Dominici et al [58] showed a worsening of tensile strength and ductility when CSS was incorporated into bio-based high-density polyethylene (bio-HDPE). The described decrease of the mechanical properties was ascribed to the low aspect ratio of the CSS particles as well as their poor adhesion to the biopolymer matrix.…”
Section: Mechanical Performance Of the Green Composite Piecesmentioning
confidence: 99%
“…Some previous studies have reported similar mechanical properties of green composites based on coffee waste derived fillers. For instance, Dominici et al [58] showed a worsening of tensile strength and ductility when CSS was incorporated into bio-based high-density polyethylene (bio-HDPE). The described decrease of the mechanical properties was ascribed to the low aspect ratio of the CSS particles as well as their poor adhesion to the biopolymer matrix.…”
Section: Mechanical Performance Of the Green Composite Piecesmentioning
confidence: 99%
“…Polyurethane is one of the polymers that play an important role in our life [11][12][13]. It plays a part in many industries; from footwear to ship-building, and it can be found in a constantly increasing variety of forms [14][15][16][17]. Automotive companies have focused recently on several polymer biocomposite materials in order to obtain materials with vibration damping and sound absorption properties in addition to light weight for reduced fuel consumption [18].…”
Section: Introductionmentioning
confidence: 99%
“…CH [ 71 ] and SCG [ 78 ] powder can be incorporated into polypropylene (PP)-based formulations, and CS powder [ 77 ] into high-density polyethylene (HDPE)-based formulations. These composites showed increased rigidity and decreased elongation at break, due to the poor interfacial adhesion between coffee by-products and the polymeric matrices.…”
Section: Coffee By-products and Their Potential For Use In The Devmentioning
confidence: 99%